Examining research into the use of data walls for teaching and learning: How are they being implemented within data use cycles?. (March 2020) - Adie, Lenore; Harris, Lois; Wyatt-Smith, Claire
Abstract: Data walls, used to display student data within schools, are a growing phenomenon internationally. Drawing on a conceptual model of data use, this systematic review examined 32 empirical sources from compulsory education settings to evaluate claims about the impact of data walls on teaching and learning. The review found details regarding goals for data walls and the displayed information, but there was limited evidence of how data analysis was used to guide improvement action and evaluation of impact. The review concluded that there is currently insufficient empirical research evidence to substantiate or refute claims about their educational effects. Highlights: This systematic review explored the impact of data walls on data use, teaching, and learning. Thirty-two articles were examined against the phases of a data use cycle. Most articles shared data wall goals and structure, few explored analysis, action, or evaluation. Major gaps exist around how walls translate to productive action within particular contexts. The review showed that evidence of the impact of data walls is currently inconclusive.